2008
DOI: 10.1007/s10616-008-9135-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a generic transient transfection process at 100 L scale

Abstract: We have developed a generic transient transfection process at 100 L scale, using HEK293-EBNA cells and PEI as the transfection reagent for the production of recombinant IgG. The process, including large-scale plasmid preparation, expression at bioreactor scale, capture, purification and, if necessary, endotoxin removal allows reproducible production of more than 0.5 g IgG for in vitro and in vivo studies. We compared the performance of two HEK cell lines, investigated the effect of conditioned medium, optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 38 publications
(66 reference statements)
1
27
0
1
Order By: Relevance
“…Cells were allowed to adapt for 2 h before transfection. Transfection mixture (0.5 liter total) was prepared with 2 mg of plasmid DNA and 5 mg of PEI (Tuvesson et al, 2008) and transferred to the culture. Four hours after transfection 5 liters of supplemented DHI medium was added to the culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were allowed to adapt for 2 h before transfection. Transfection mixture (0.5 liter total) was prepared with 2 mg of plasmid DNA and 5 mg of PEI (Tuvesson et al, 2008) and transferred to the culture. Four hours after transfection 5 liters of supplemented DHI medium was added to the culture.…”
Section: Methodsmentioning
confidence: 99%
“…Large-Scale Transient Transfection Suspension Cultures. The cultures with MRP2 and BCRP were performed according to the largescale protocol published earlier (Tuvesson et al, 2008). The transfection was carried out at a cell density of 1.0 ϫ 10 6 cells/ml in half of the final volume for several hours, after which the remaining medium was added.…”
Section: Att Adaption Of Transporters and Entry Vector Sequence Analy-mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these experiments observed the use of 100% conditioned media during transfection resulted in a reduced titer. This observation is also consistent with reported studies in literature Tuvesson et al This study also found that 50% conditioned media did not significantly reduce protein levels. Tuvesson et al (2008) found that the use of more than 25% conditioned media during transfections impairs transfections.…”
Section: Tangential Flow Filtrationsupporting
confidence: 93%
“…High titer processes, however, utilize high density cultures with cell concentration and medium exchange steps prior to transfection. All such protocols published to date, utilize external batch centrifugation, using lab-scale centrifuges, for media exchange and cell concentration Tuvesson et al 2008). This method is typically limited in scale to 20 liters or less, as cells are typically processed in batches of 6-L or less (i.e, 6 x 1-L bottles).…”
Section: Introductionmentioning
confidence: 99%